Persepsi Wisatawan Eropa Terhadap Paket Wisata Pedesaan (Rural Activity) Pada D’karang Homestay, Bali - Ni Putu Evi Wijayanti (JURNAL BISNIS HOSPITALITI, 2020)
Rural tourism is one tour package that is highly desirable for foreign tourists, especially European tourists. Rural tourism has an important role and provides many benefits in the tourism sector for rural communities. When tourists travel to rural areas, they indirectly help local communities in developing rural areas and living standards. Furthermore, homestay is one of the criteria for a tourist village. Homestay is a product of the tourism industry where tourists can meet directly with local residents. Tourists who stay at the homestay and given an offer of rural tour packages, can be an opportunity for the community to attract tourists to stay longer by enjoying a variety of natural and cultural activities in the tourist village. This study aimed to determine the perceptions of European tourists on rural tour packages at D’Karang Homestay. The benefit of this research is to add references in tourism studies especially about the perceptions of European tourists on rural tourism packages. The research methods used were observation, interview, questionnaire and documentation. This research revealed European tourist perceptions of the rural tour packages offered by D’Karang Homestay but there are still shortcomings that need to be corrected.